Impact of Psychoneurobics Charging on Homeopathy Medicines for Nephrology Patients: Harnessing the Power of Prayer and Visualization for Enhancing Homeopathy Treatment in Nephrology Patients (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Psychoneurobics uses visualisation of colours and prayers to the divine source of light, the creator of the entire universe for help and healing. It believes that prayer to the almighty can help to direct the light energy into mediums which in turn can help in charging them to result in beneficial results. In the past 15 years Dr. Chandrashekhar Tewari has through various scientific instruments proved the charging of water and food which have in-turn helped in various healings both physiological and otherwise. The same principals of charging water and food has been applied on charging(in the form of praying and seeking the almighty’s blessings and empowerment) Homeopathy medicines while being dispensed for cases of Nephrology cases being handled at Earth Saviour Foundation, with affect which have been found to be having statistical significance.